Pragmática histórica del español rioplatense. Actos directivos y estrategias de mitigación en correspondencia femenina delsiglo XIX Historical pragmatics of Rio de la Plata Spanish. Directive acts and mitigation strategies in 19th century female correspondence - Albitre Lamata, Paula (Studia Linguistica Romanica)
This paper focuses on the study of directive acts in 19th-century Rio de la Plata Spanish. For this purpose, a specialized microcorpus of 74 private letters written by women to their husbands has been compiled. Using a corpus-driven methodology, both the different linguistic constructions in which these speech acts are performed and their (dis)politeness values have been analyzed. The results obtained from this research reveal significant differences compared to Peninsular Spanish of the same period, as evidenced by a high frequency of direct constructions and the use of attenuating mechanisms.